2006
DOI: 10.2193/0091-7648(2006)34[1376:usgmpt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Using Sharp-Tailed Grouse Movement Patterns to Guide Release-Site Selection

Abstract: Prairie grouse populations are difficult to reestablish after extirpation. Following translocation, distances individuals move from the release site appear to affect restoration success. Previous authors have suggested assessing lek, nest‐brood, and winter habitat when selecting release sites. We examined movement of 131 (66 M and 65 F) radiomarked Columbian sharp‐tailed grouse (Tympanuchus phasianellus columbianus) translocated during 1999–2002 as part of management effort to restore populations to historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Previous studies have suggested that territorial interactions with conspecifics or competition for limited and patchily distributed resources can influence post‐release movements of translocated animals (Allen, Franzreb & Escano, ; Armstrong, ; Clarke & Schedvin, ; Dunham, ; Coates et al ., ). Although prairie‐chickens are generally not territorial, males do defend small areas on leks (Robel & Ballard, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have suggested that territorial interactions with conspecifics or competition for limited and patchily distributed resources can influence post‐release movements of translocated animals (Allen, Franzreb & Escano, ; Armstrong, ; Clarke & Schedvin, ; Dunham, ; Coates et al ., ). Although prairie‐chickens are generally not territorial, males do defend small areas on leks (Robel & Ballard, ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, during the early spring resident males remain close to favored leks and only make infrequent large‐scale movements (Hamerstrom Jr & Hamerstrom, ; Patten et al ., ). These same patterns have indeed been observed in translocated grouse as well; translocated females were found to have greater movements than males (Toepfer, ; Musil, Connelly & Reese, ; Coates et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As predicted, T1s moved significantly more per day compared to all others. The pattern of newly translocated individuals moving large distances has been observed in a variety of taxa including Agassiz's desert tortoise ( Gopherus agassizii ; Nussear et al ), Columbian sharp‐tailed grouse ( Tympanuchus phasianellus columbianus ; Coates et al ), and swift foxes ( Vulpes velox ; Moehrenschlager and Macdonald ). For sage‐grouse in our study, these expansive movements drastically decreased after the first year, with T2s exhibiting smaller annual movement patterns than residents after their first year.…”
Section: Discussionmentioning
confidence: 98%
“…In prairie grouse, a species that has been difficult to restore, individuals move substantial distances away from the release site (Coates, Stiver & Delehanty, 2006). Translocated individuals have also been documented returning to the original site of capture (Carrie et al, 1996;Clarke & Schedvin, 1997;Fancy, 1997).…”
Section: Introductionmentioning
confidence: 99%